2021
DOI: 10.20452/pamw.16071
|View full text |Cite
|
Sign up to set email alerts
|

Overhydration as a modifiable cardio-vascular risk factor in patients undergoing hemodialysis

Abstract: What's new?Mortality in end-stage renal disease is exceptionally high comparing to age-and sex-matched general population with cardio-vascular events as the leading cause of death. Chronic fluid overload, a non-traditional cardio-vascular risk factor, seems to have a critical contribution to this dramatic outcome. This study aimed at providing statistical evidence for the relation between overhydration and high cardio-vascular mortality in end-stage renal disease. We confirmed that fluid overload is an indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This natriuretic peptide tends to increase in PD patients when compared to a healthy population, and scientists point out that the dialysis method has no influence on its level in the blood [59]. NT-pro-BNP tends to increase in individuals with fluid excess during clinical studies on various methods of estimating hydration status [22,30,32,[42][43][44]49,60,61]. It was elevated during the increase in protein clearance during peritoneal dialysis [44], associated with pleural effusion and IVC diameter [30,61] and ECW/TBW ratio [32,42,43,60] but not with peripheral edema [19,30].…”
Section: Serum Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…This natriuretic peptide tends to increase in PD patients when compared to a healthy population, and scientists point out that the dialysis method has no influence on its level in the blood [59]. NT-pro-BNP tends to increase in individuals with fluid excess during clinical studies on various methods of estimating hydration status [22,30,32,[42][43][44]49,60,61]. It was elevated during the increase in protein clearance during peritoneal dialysis [44], associated with pleural effusion and IVC diameter [30,61] and ECW/TBW ratio [32,42,43,60] but not with peripheral edema [19,30].…”
Section: Serum Markersmentioning
confidence: 99%
“…In a research study involving 179 non-dialysis CKD patients in all stages, OH measured by BCM correlated with urinary protease activity and progression of renal dysfunction, as well as with increases in NT-pro-BNP and systolic blood pressure [42]. Schwermer et al indicated that male gender, smoking, diabetes, and cardiovascular incidences were connected to OH [49]. Scientists noticed also that OH induced an increase in NT-pro-BNP and troponin concentration which was interpreted as cardiovascular toxicity of water surplus.…”
Section: Serum Markersmentioning
confidence: 99%
“…End-stage renal disease (ESRD) can increase mortality, impose financial burden and reduce the quality of life [4][5]. Nevertheless, studies evaluating the performance of eGFR equations in patients with ESRD not on dialysis remain scarce.…”
Section: Introductionmentioning
confidence: 99%